IMPRESSION MANAGEMENT TACTICS: ITS RELATIONSHIP TO COLLEGIATE INTERPERSONAL RELATIONSHIP - Libayne-Factora, Magnolia (International Journal of Psychosocial Rehabilitation, 2020)
This paper ascertained the impression management tactics of deans in one university. It looked into the profile of the different college deans and related it to collegiate interpersonal relationship. It further investigated the various impression management employed by the deans and how these are assessed by both the deans and the faculty. Eventually, a comparison of the assessment was made. There were 365 respondents in this study who come from 42 colleges university-wide. The quantitative method was utilized in this study. It also employed the descriptive correlational method which is qualitative in nature. The study used the quantitative method of research. Specifically, it employed the descriptive correlational research method which is quantitative in nature. The descriptive method was used considering that the study ascertains the profile of the college deans, the impression management tactic used and the reasons of the college deans for using their impression management tactics. On the other hand, the correlational part involves the investigation of the significant difference in the impression management tactics of the College Deans as assessed by the teachers and College Deans themselves; the significant difference in the impression management tactics of the College Deans according to their profile variables. The results revealed that CSU College Deans utilize eclecticism in their impression management in the workplace. The utilization of this impression management tactic is primarily dependent on every situation that the deans find effective. In utilizing an eclectic approach, the deans have healthy interpersonal outcomes to be liked, to be perceived competent and to be perceived as good performers by their subordinates. Thus, it can be said that the college deans used their impression management tactic successfully.Finally, it can be said that the CSU College deans utilize good impression management tactic which is an essential competency for an effective and productive organization.